Corporate Social Responsibility in Cameroon (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Corporate Social Responsibility (CSR), a concept whereby firms are expected to surrender some of their profits for the welfare of their surrounding communities is becoming increasingly evident in the practices and activities of many companies in Cameroon. Companies in Cameroon are making efforts towards social responsibility in their host communities such as provision of public utility services, educational and health facilities, poverty alleviation, support for local culture, sports and others. However, it becomes imperative that companies establish their CSR policies to ensure effectiveness in the practice and implementation of CSR. This is because, the absence of CSR Policy at the level of the State and lack of oversight agencies provide room for companies to establish and act nonchalantly towards Corporate Social Consciousness to their operating environment and communities. This explains why CSR efforts of companies in Cameroon embrace ineffectiveness even though the companies might have CSR policies in place.